Characterization and Determination of pH, Alcohol, and Temperature Tolerance of Microorganisms Recovered From Vegetable Samples - Ismail Babatunde Onajobi; Oyindamola John Samson; Hafeez Aderinsayo Adekola; Suliamon Adebisi Aina; Titilola Fausat Salisu; Muinat Olanike Kazeem; Inumidun Esther Ogunlana; Faidat Ayomide Adetunji; Mary Rereloluwa Nubi; Raliat Omobolanle Salau; Lawrence Olubukunade Adebajo (University of Sultan Ageng Tirtayasa, 2024)
This study aims to investigate the spectrum of bacteria and yeasts present in soaked vegetables and their resilience to varying pH levels, alcohol, and temperatures. Four samples were collected from Ago-Iwoye market, and initial isolation and identification were conducted using streaking techniques and biochemical tests. Standard procedures were employed to assess bacteria and yeast tolerance to different pH levels, alcohol concentrations, and temperature ranges. The biochemical tests identified microorganisms, including Lactobacillus spp., Lactobacillus spp., Enterococcus spp., Leuconostoc spp., Escherichia coli, and Saccharomyces cerevisiae. Bacterial and yeast isolates demonstrated viability at both 10°C and 45°C, while no visible growth occurred at 60°C, indicating the respective heat resistance of these microorganisms commonly found in vegetable samples. The evaluation of microbial tolerance to varying pH conditions is pivotal for exploring adaptability in food processing and digestion, particularly in fermentation processes. The research concludes the microbial diversity present, distinguishing between beneficial and potentially harmful strains.